Comparison of Perinatal Outcomes for All Modes of Second Stage Delivery in Obstetric Theaters: A Retrospective Observational Study. Issue 1 (March 2022) - Gurney, L.; Wattar, B.H.A.I.; Sher, A.; Echevarria, C.; Simpson, H.
Abstract : ( BJOG . 2021;128:1248–1255) The World Health Organization recommend techniques to encourage vaginal delivery to mitigate unnecessary cesarean deliveries and the associated complications. These techniques include Keilland's rotational forceps delivery, direct forceps delivery, manual rotation followed by forceps delivery, or ventouse delivery. Although this study demonstrated that Keilland's rotational forceps delivery may be associated with successful vaginal delivery, some clinicians currently avoid instrumental delivery to evade maternal or neonatal harm, which ultimately leads to less skilled instrumental delivery and therefore, a riskier alternative. This study evaluated the effectiveness and safety of instrumental vaginal delivery techniques. In addition, it compared adverse perinatal outcomes between instrumental delivery and primary emergency cesarean section at full dilation (pEmCS).